Protective effect of Berberis vulgaris on Fenton reaction-induced DNA cleavage - Nooshin Sadat Asadi; Mohammad Mehdi Heidari; Mehri Khatami (Mashhad University of Medical Sciences, 2019)
Objective: Berberis vulgaris contains antioxidants that can inhibit DNA cleavage. The purpose of this study was to evaluate the antioxidant and protective activity of B. vulgaris on DNA cleavage. Materials and Methods: In this study, the antioxidant capacity of B. vulgaris was investigated using DPPH and its protective effect was evaluated on pBR322 plasmid and lymphocyte genomic DNA cleavage induced by Fenton reaction, by DNA electrophoresis. Results: Aqueous extract of B. vulgaris presented dual behavior with a potent antioxidant activity at 0.25and 0.75mg/ml for pBR322 plasmid and lymphocyte genomic DNA, respectively, but a pro-oxidant activity was observed at higher concentrations. Conclusion: Our results indicated that B. vulgaris extract an inhibit Fenton reaction-induced DNA cleavage and oxidative cleavage of double-stranded DNA assay is a powerful technique that can be used to determine the antioxidant and pro-oxidant properties of a compound on cellular components such as DNA.